Modeling and analysis of polarization effect on signal intensity profile of two-dimensional page data in holographic data storage system - Shimada, Ken-ichi; Itoh, Masahide (Optics Communications, 2021)
The data transfer rate as well as recording data density of holographic data storage systems can be improved by using a high-numerical aperture (NA) objective lens. However, a high-NA lens is likely to develop an inhomogeneous intensity profile of a reproduced holographic page data based on the polarization state of reference and signal beams during recording and readout. We analytically formulated how the polarization state of reference and signal beams during recording and readout affects signal intensity on a camera over the entire area of the page data. When Born approximation is applicable, we found that the signal amplitude of the reproduced page data can be expressed by multiplying signal amplitude calculated from scalar diffraction theory by an attenuation coefficient dependent on the polarization state. This means the intensity profile of the page data, taking polarization effect into account, can be calculated without using vector diffraction theory which requires high computational complexity. The validity of this analytical formulation was confirmed through a comparison of experiments with numerical analysis. The formulation led to a new method of increasing signal intensity of the page data area deteriorated by the polarization effect. •Analytical formulation of polarization effect on reproduced holographic image.•The analytical formulation does not need calculation using vector diffraction theory.•High NA objective lens induces intensity decrease in the Bragg-degenerate direction.